Brain Networks, Emotion Components, and Appraised Relevance. (July 2018) - Sander, David; Grandjean, Didier; Scherer, Klaus R.
Modeling emotion processes remains a conceptual and methodological challenge in affective sciences. In responding to the other target articles in this special section on "Emotion and the Brain" and the comments on our article, we address the issue of potentially separate brain networks subserving the functions of the different emotion components. In particular, we discuss the suggested role of component synchronization in producing information integration for the dynamic emergence of a coherent emotion process, as well as the links between incentive salience ("wanting") and concern-relevance in the elicitation of emotion.